The study of frequency of malignancy and its types in surgical jaundice; a tertiary care experience - Anwar, Jamal; Shabbir, Usama; Mohammad Sohail Asghar; Hafiz Syed Zaigham Ali Shah; Afzal, Ameer; khalid Masud Gondal (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of malignancy and its types in patients presenting with surgical jaundice in a tertiary care setting. Method: The cross-sectional study was conducted at the North Surgical Ward, Mayo Hospital, Lahore, Pakistan, from May 8 to November 8, 2020, and comprised patients of either gender with a diagnosis of surgical jaundice made on the basis of history, clinical examination, haematological and biochemical reports and radiological investigations. All patients were managed as per the guidelines for surgical jaundice with injection vitamin K intramuscular, hydration with intravenous fluids, avoidance of constipation by lactulose or neomycin, vitals and urine output monitoring and prophylactic antibiotics. Demographic data as well frequency of malignancy were noted using a predesigned proforma. Data was analysed using SPSS 21. Results: Of the 95 patients, 51(53.7%) were male and 44(46.3%) were female. The overall mean age was 49.96±16.54 years (range: 18-80 years). A total of 19(20%) cases had body mass index <30. Malignancy was identified in 50(52.6%) cases; 14(28%) gallbladder, 4(8%) head of pancreas, 9(18%) peri-ampullary carcinoma, 7(14%) cholangiocarcinoma, 6(12%) Klastkin tumour, 5(10%) hepatocellular carcinoma, and 5(10%) metastatic tumour. Conclusion: More than half of the surgical jaundice cases had malignancy, gallbladder being the most affected site. Key Words: Surgical jaundice, FNAC, Peri-ampullary carcinoma, Klastkin tumour, Hepatocellular carcinoma.